HUBUNGAN TINGKAT PENGETAHUAN ORANG TUA TENTANG KESEHATAN GIGI DAN MULUT TERHADAP KEJADIAN GIGI KARIES PADA ANAK USIA 3 -14 TAHUN DI LINGKUNGAN PERUMAHAN WISMA MAS TAHAP 3 RT 016 KUTA JAYA - Reskawati, Shindy Ainun; Sulaeman, Sulaeman; Pratiwi, Ayu (Nusantara Hasana Journal, 2022)
Dental caries disease in children is common and often occurs but does not get the attention of parents. The purpose of this study was to determine the relationship between the level of parental knowledge about dental and oral health on the incidence of dental caries in children aged 3-14 years in the residential neighborhood of Wismamas stage 3 RT 016 Kuta Jaya. Probability sampling was cluster sampling using a cross sectional approach using a quantitative method of respondents 113. Instruments in the form of a questionnaire and an observation sheet containing an observation table consisting of the number of respondents. The results of the normality test showed that the knowledge of parents with asymp, sing (2-tailed) 0.00 (<0.05) and the incidence of dental caries with asymp, sing (2-tailed) value 0.00 (<0.05) and using bivariate analysis with chi-square test results obtained p value 0.023 means <0.05.